2006
DOI: 10.1002/jmv.20720
|View full text |Cite
|
Sign up to set email alerts
|

Rapid diversification of measles virus genotypes circulating in Morocco during 2004–2005 epidemics

Abstract: Measles virus strains circulating in six different regions in Morocco during 2004-2005 were analysed. They were genotyped using two different methods: the recently developed method based on real-time PCR amplification and melting curve analyses, and the conventional method based on nucleic acid sequencing and phylogenetic analysis of 456 nucleotides of the 3'-region of the nucleoprotein (N) gene sequence. Five genotypes (A, B3.2, C2, D7 and D8) were shown to be circulating during this period. Previous studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…This state borders Cameroon, where a 1997 lineage IV virus (HQ131960, Fig ) was reported (Kwiatek et al., ). It is tempting to think that viruses of lineage IV‐NigB were first introduced into Nigeria from Cameroon and then evolved into lineage IV‐NigA viruses due possibly to genetic drift following in‐country transmission, as has been suggested for measles viruses (Santibanez et al., ; Alla et al., ; Waku‐Kouomou et al., ). Further in‐depth genetic analysis using next‐generation sequencing is planned to confirm this hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…This state borders Cameroon, where a 1997 lineage IV virus (HQ131960, Fig ) was reported (Kwiatek et al., ). It is tempting to think that viruses of lineage IV‐NigB were first introduced into Nigeria from Cameroon and then evolved into lineage IV‐NigA viruses due possibly to genetic drift following in‐country transmission, as has been suggested for measles viruses (Santibanez et al., ; Alla et al., ; Waku‐Kouomou et al., ). Further in‐depth genetic analysis using next‐generation sequencing is planned to confirm this hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…The entire coding sequence of the Hoedts was also analyzed. As the sequences of the complete genome of the reference strain for genotype C2 (Maryland.USA/77) was not available on Genbank, the genome of the strain M185 [Alla et al, 2006] was sequenced and used as the wild‐type strain for comparison. The results showed that the amino acid sequence divergence was 1.6%, 2.3%, 6.5%, 2.6%, 1.4%, and 0.9% for N, P, M, F, H, and L, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The position of MeV214 increases the distance between the primer binding site and the 3′ terminus of N-450, which improves sequence quality. Unlike several previously published primer pairs [11,[18][19][20][21], the new primers allow sequencing of the entire N-450 which is required to assign a genotype [32] and to submit the sequence to MeaNS [2], the global measles sequence database. In this study, only one representative for each genotype was sequenced.…”
Section: Comparison Of Primers Mv60/mv633 With Primers Mev216/mev214mentioning
confidence: 99%
“…Several new MeV genotypes have been described since the introduction of the standard genotyping method [15][16][17]; however, only limited sequence data were available for the primer binding sites of the more recent strains and the analytic sensitivity of the primers had not been evaluated. Several laboratories have introduced nested PCR assays, some of which do not amplify the complete N-450 [11,[18][19][20][21] or do not provide data for sensitivity and specificity [9,10].…”
Section: Introductionmentioning
confidence: 99%